Effect of leukotriene receptor antagonist therapy on the risk of asthma exacerbations in patients with mild to moderate asthma: an integrated analysis of zafirlukast trials. Issue 6 (1st June 2000) - Barnes, Neil C; Miller, Christopher J
Abstract : BACKGROUND: Asthma exacerbations contribute substantially to morbidity, and their reduction is an important therapeutic objective. In this integrated analysis the risk of asthma exacerbations was assessed during treatment with the leukotriene receptor antagonist zafirlukast. METHODS: Data were collected from all five double blind, multicentre, randomised, placebo controlled, 13 week trials of zafirlukast 20 mg twice daily performed in steroid-naive patients with mild to moderate asthma. Exacerbation data were collected prospectively during monitoring of adverse events and concomitant medication use. Pooled data were used to assess the relative risk of asthma exacerbations using three definitions: worsening of asthma leading to withdrawal from the study; requirement for additional anti-asthma therapy (excluding increased short acting β2 agonist use); and requirement for oral corticosteroid therapy. RESULTS: The proportion of patients with an asthma exacerbation leading to withdrawal was consistently lower in the group treated with zafirlukast 20 mg twice daily than in the placebo group. Overall, the risk of an asthma exacerbation requiring withdrawal from zafirlukast therapy was approximately half that of placebo (odds ratio 0.45; 95% CI 0.26 to 0.76; p = 0.003). Similar results were observed for exacerbations requiring additional control medication (odds ratio = 0.47; 95% CI 0.30 to 0.74; p = 0.001) and oral corticosteroid rescue (odds ratio = 0.53; 95% CI 0.32 to 0.86; p = 0.010). CONCLUSIONS: Zafirlukast in a dose of 20 mg twice daily reduces the risk of asthma exacerbations and the need for additional anti-asthma therapies, fulfilling an important goal of control medication in patients with mild to moderate asthma.